The Assessment of Investment into Risk Management of a Company - Skvarciany, Viktorija; Olechnovič, Lilita (Jaunųjų mokslininkų darbai, 2017)
Under market economy conditions business activities are very dynamic and that leads to the uncertainty of forecasted results and operational risk. Seeking to ensure a company’s development, its success and income, it is necessary to assess risk while taking decisions therefore it is important to invest into operational risk management. The aim of the research is to analyze and evaluate investment into operational risk management if return from such investment is not expected. Research objectives: to analyse the concept of operational risk management and risk assessment and management methods; to analyse and assess operational risk management environment of a particular company (case study). Research methods: scientific literature analysis, data collection and systematization, qualitative research.